ANALISIS TREN PENELITIAN AUGMENTED REALITY DALAM PENDIDIKAN DASAR DI DUNIA: TINJAUAN R BIBLIOSHINY - M. Nuzulul Ulum; Ahmad Bayu Permana; Adhi Setiyawan (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study analyzes global research trends on Augmented Reality in elementary education using a bibliometric approach through R Biblioshiny, based on 104 Scopus-indexed publications from 2019 to 2025. The findings indicate that Augmented Reality research is in a stable growth phase, with a publication growth rate of 6.24%, an average of 16.81 citations per document, and an international collaboration rate of 24.04%. Keyword visualizations reveal dominant themes such as augmented reality, students, motivation, learning systems, and elementary school, indicating a strong focus on pedagogical effectiveness and immersive learning experiences. Source and authorship analyses show that academic influence remains fragmented with moderate H-index values, while network collaboration illustrates clusters that are not yet fully integrated globally. These findings affirm that Augmented Reality research in elementary education is evolving toward an interdisciplinary approach, particularly in science learning, the enhancement of critical thinking skills, and the integration of emerging technologies such as mobile learning and the metaverse.